2021
DOI: 10.3390/medicina57020132
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Monitoring of Hypnosis and Nociception-Antinociception Balance during General Anesthesia—A New Era in Patient Safety Standards and Healthcare Management

Abstract: The development of general anesthesia techniques and anesthetic substances has opened new horizons for the expansion and improvement of surgical techniques. Nevertheless, more complex surgical procedures have brought a higher complexity and longer duration for general anesthesia, which has led to a series of adverse events such as hemodynamic instability, under- or overdosage of anesthetic drugs, and an increased number of post-anesthetic events. In order to adapt the anesthesia according to the particularitie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that patients did not respond to intraoperative stimuli when qNOX levels were well controlled [19,20,28]. In a study of 60 patients who underwent general anesthesia with propofol and remifentanil, Jensen et al demonstrated that qNOX can detect subtle changes in nociceptive balance by showing a series of significant correlations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients did not respond to intraoperative stimuli when qNOX levels were well controlled [19,20,28]. In a study of 60 patients who underwent general anesthesia with propofol and remifentanil, Jensen et al demonstrated that qNOX can detect subtle changes in nociceptive balance by showing a series of significant correlations.…”
Section: Discussionmentioning
confidence: 99%
“…All patients fasted from midnight and received glycopyrrolate 0.004 mg/kg via intramuscular injection and famotidine 20 mg intravenously before entering the operating room. After entering the operating room, the blood pressure, heart rate (HR), and qNOX [19,20] levels were measured to establish the baseline under standard monitoring. Both groups underwent an ultrasound-guided peripheral nerve block (PNB) before anesthesia.…”
Section: Interventionsmentioning
confidence: 99%
“…Its score ranges from 0 to 100, a low score meaning that the patient is able to process nociceptive stimulus. The Surgical Pleth Index (SPI) is rather based on the measurement of the orthosympathetic hemodynamic response to noxious stimulation, and uses normalized heartbeat intervals (HBIs) and plethysmography wave amplitude for its calculation ( Rogobete et al, 2021 ). The PDR and the GSR are also used in anesthesia to assess the sympathetic tone but have not yet been studied in detail in patients with DoC and LIS.…”
Section: Reflections and Future Directionsmentioning
confidence: 99%
“…Unlike other components of general anesthesia, such as hypnosis and muscle relaxation (1), currently, there is no gold standard for monitoring a patient's response to noxious stimuli during intraoperative analgesia (2). Due to the interpatient variability in response to nociceptive input, optimal opioid titration remains a challenge for anesthetists.…”
Section: Introductionmentioning
confidence: 99%